'An extreme case': the removal of rock art from uMhwabane (eBusingatha) rock art shelter, Bergville, KwaZulu-Natal - Hollmann, J. C.; Msimanga, L. (Southern African Humanities, 2008)
uMhwabane Shelter (also known as eBusingatha Shelter) is a rock art site alongside the eBusingatha River in the amaZizi Traditional Authority Area. It is one of KwaZulu-Natal’s problem rock art sites. Today it still contains at least 50 hunter-gatherer paintings but there used to be many more. As with other easily accessible rock art sites that have no access control, the art has suffered from vandalism. Authorities responded by removing some 31 painted rocks at the time of the visit of the British royal family to South Africa in 1947. The institutions entrusted with their care subsequently neglected the art. Action is now being taken to conserve and display the removed rock art. In this paper we piece together oral traditions, documents and images to tell the history of an extreme case of archaeological intervention, its consequences and future prospects.